(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Mathematical analysis is an initial and at the same time main branch of higher mathematics. With the intensive development of mathematics, its enrichment of new concepts and new ideas, the scope of application to various branches of science and technology expands, mathematics penetrates into all spheres of human activity. Without knowing the methods of mathematical analysis, it is difficult to understand the processes taking place in nature, the issues considered in the natural science and technical literature. But the practical applications of the concrete integral are not limited to this, and with its help many more problems find their solution.